(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Goiter is a common entity in this part of the world. The objective of this study was to analyze the clinical presentations, operative findings and histopathological results of 100 patients with goiter. Subjects & Methods: This study was conducted on 100 patients who were presented with goiter, and were operated on in Al-Kadhimiya Teaching Hospital during the period from January 2000 through January 2001. The diagnosis of goiter has been based on the clinical examination, thyroid function tests, ultrasonography and thyroid scan. The thyroid specimens obtained by surgical intervention where sent for histopathological study. The data obtained were analyzed and the results were evaluated. Results: Depending on clinical examination the thyroid swellings were classified into solitary nodule 30%, multinodular goiter 50% and diffuse goitre 20%. Subsequent classification of goiter on the bases of intraoperative findings and histopathological examination revealed an increase in the number of multinodular goiter to 72%. The total number of patients with confirmed solitary nodule is 20 (20%). The histopathological examination showed that simple cyst constituted 50% of solitary nodules, adenoma 40% and malignancy 10%. The total incidence of malignancy in goiter is 4%. The overall correct prediction of histopathological diagnosis by FNA is 75%. Conclusions: The true diagnosis of MN goiter should be based on clinical examination, intraoperative findings and histopathological confirmation. More than 33% of patients with solitary thyroid nodule under clinical examination were found to have additional nodules at operation and by histopathological examination. The incidence of malignancy in goiter in general is 4%. The diagnostic accuracy of FNAC was 75%. Key words: Goiter, Thyroid surgery, FNAC, Histopathology. Iraqi J Med Sci, 2004; Vol. 3 (1): 68-72